A Novel Fluorescent Dye Extracted from Buddleja officinalis for Labeling Mitochondria after Fixation. (3rd June 2022) - Yang, Ying; Kim, Ok-Su; Kim, Byunggook; Liu, Guo; Song, Jianan; Liu, Danyang; Ma, Guowu; Kim, Young; Kim, Okjoon
Abstract : Mitochondria are versatile organelles and function by communicating with cellular ecosystems. The fluorescent colocalization analysis after fixation is a highly intuitive method to understand the role of mitochondria. However, there are few fluorescent dyes available for mitochondrial staining after fixation. In this study, a novel fluorescent dye (BO-dye), extracted from Buddleja officinalis, was applied for mitochondrial staining in fixed immortalized human oral keratinocytes. The BO-dye (excitation: 414 nm, emission: 677 nm) is a small fluorescent molecular dye, which can cross the cytomembrane without permeabilization. We assume that the BO-dye could aggregate and bind to the mitochondria stably. BO-dye exhibited a mega-Stokes shift (>250 nm), which is an important feature that could reduce self-quenching and enhance the signal-to-noise ratio. Analysis of photophysical properties revealed that the BO-dye is temperature and pH insensitive, and it exhibits superior photostability. These results indicate that BO-dye can be considered an alternative fluorescent dye for labeling mitochondria after fixation.